"Forever in Our Hearts" Online: Virtual Deathscapes Maintain Companion Animal Presence. (November 2021) - Eason, Fenella
Embodying companion animals as part of ourselves obliges a similar grief, when they die, to the anguish that follows the death of a human partner, relative, or close friend. Individual mourning may fail to assuage pain that is further intensified when the bereaved human lacks society's recognition not only of their grief but also of the intrinsic worth of their deceased animal companion. Such disenfranchised grief may lead to isolation and to withdrawal from social integration. However, diverse memorials recorded online, and reasons for their inclusion in cyberspace, are enabling validation of the lives of nonhuman animal companions by both isolated and more sociable pet-bereaved mourners.